Semi solid metal pouring temperature effects on mechanical properties of Al-Si alloy - Nurul Hidayati, Salleh (2012)
In this study, mechanical properties and morphology study of semi-solid metal Al-Si alloy casting was investigated. The sand castings were conducted at three different pouring temperatures. The pouring temperatures for the investigation were 620°C, 640°C and 695°C. The three different samples were tested for their properties such as strength, hardness and the microstructure. Tensile test was conducted using Shimadzu Universal Testing Machine. Hardness was measured by Matsuzawa Rockwell Hardness Testing machine. Microstructure of cast samples were observed using LEICA DME working microscope. The different pouring temperatures caused different cooling rates on the cast samples. The results and observation indicates that a lower temperature produced good quality castings with the maximum values of strength and hardness of 124.34 N/mm2 and 62.3 respectively.From metallographic study, primary phase of cast sample at the lower pouring temperature was globular structure while dendrite structure occurs due to a higher pouring temperature. The lower pouring temperature provides a finer microstructure and high hardness samples due to faster cooling rate produced at lower pouring temperature.